2014
DOI: 10.1902/jop.2013.130318
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Rich Plasma, Low‐Level Laser Therapy, or Their Combination Promotes Periodontal Regeneration in Fenestration Defects: A Preliminary In Vivo Study

Abstract: LLLT, PRP, or their combination all promoted NC formation with a functional periodontal ligament. The combination PRP/LLLT did not show additional positive effects compared to the use of either therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…Recent in vitro studies have demonstrated that PRP exerts positive effects on gingival fibroblasts, 16 oral osteoblasts, 17 and periodontal ligament fibroblasts 18 . A preliminary in vivo study recently published by the present authors’ group showed that PRP promoted NC formation with a functional periodontal ligament in fenestration defects in rats 2 . However, the precise role of platelet concentrates in periodontal tissue regeneration still needs to be better clarified.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Recent in vitro studies have demonstrated that PRP exerts positive effects on gingival fibroblasts, 16 oral osteoblasts, 17 and periodontal ligament fibroblasts 18 . A preliminary in vivo study recently published by the present authors’ group showed that PRP promoted NC formation with a functional periodontal ligament in fenestration defects in rats 2 . However, the precise role of platelet concentrates in periodontal tissue regeneration still needs to be better clarified.…”
mentioning
confidence: 75%
“…Periodontal regeneration involves the formation of new alveolar bone, cementum, and functional periodontal ligament. Newer periodontal treatment modalities to enhance regeneration include the use of mesenchymal stem cells (MSCs) 1 and platelet‐rich plasma (PRP) 2 …”
mentioning
confidence: 99%
“…With regard to the treatment of periodontal bone defects, Nagata et al. analyzed the influence of platelet‐rich plasma, low‐level laser therapy (660‐nm diode laser), separately or combined, on the healing of periodontal fenestration defects in rats. Low‐level laser therapy and platelet‐rich plasma, separately or combined, all promoted new cementum formation with a functional periodontal ligament.…”
Section: Low‐level Laser Therapymentioning
confidence: 99%
“…With regard to the treatment of periodontal bone defects, Nagata et al (29) analyzed the influence of platelet-rich plasma, low-level laser therapy (660-nm diode laser), separately or combined, on the healing of periodontal fenestration defects in rats. Low-level laser therapy and platelet-rich plasma, separately or combined, all promoted new cementum formation with a functional periodontal ligament.…”
Section: A Comparative Study Of the Effect Of Demineralized Bone Matrmentioning
confidence: 99%